Towards evening paratransit services to complement scheduled public transport in Cape Town: exploring alternative policy interventions from the minibus-taxi industry's perspective - Plano, Christopher Evan (Department of Civil Engineering, 2020)
Cities across low and middle income countries are seeking to improve public transport services, but the presence of large numbers of independent paratransit operators complicate reforms. City officials often seek to eliminate paratransit services in favor of scheduled services, typically bus rapid transit, yet this has proven impossible to achieve. Cape Town is one such city, whose planning officials recognize that the transition to and operating costs of new scheduled services are unsustainable. Reconsidering the reform approach, the City has acknowledged a continued role for paratransit services primarily as feeders to scheduled services. This raises the question of how complementary service quality can be obtained at transfer points between scheduled and unscheduled services. The research seeks to assist operators in sharing their perspectives outside of a City-structured engagement process and to assist City officials in understanding what reform paths will be most feasible based on paratransit operator acceptability and cost to the City. To do so, this study uses a mixed methods approach using a naturally occurring example that mirrors the hybrid network arrangement as espoused by the City. The feasibility of interventions to improve evening service quality complementarity, specifically related to mismatched service span and long off peak headways, is explored with minibus-taxi operators. The two key stakeholders among operators are vehicle owners and drivers who have differing perspectives on the business and reform. Understanding these differing perspectives is critical to successful implementation of future reforms as past attempts have been met with considerable resistance from the industry. Driver perspectives were captured through a stated choice survey while owners were engaged through structured focus groups. Costs of interventions were estimated and combined with stakeholder data to indicate which interventions to extend service into the evening and maintain short headways are most likely to be successful if attempted by City officials. Results indicate that to extend paratransit services to match scheduled modes, improvements in rank (terminal) security, an increase in fares, or an operating deficit payment incentive are the most feasible of seven interventions explored. The first two require little transition effort or cost to the City but will not address potentially long headways; the third most feasible intervention addresses both service quality issues yet represents a larger burden for the City. Aligned with experience from previous reforms to eliminate paratransit in favor of contracted, scheduled services, this research finds that corporatization of paratransit operators may be less feasible than other interventions explored; this suggests that the City's policy shift is appropriate and that alternative approaches to paratransit reform that are less costly and require less onerous changes from status quo operations are feasible. By undertaking these alternatives, limited government budgets can be spent more effectively and efficiently so public transport reform reaches more residents more quickly.